SIKAP SISWA TERHADAP PEMBELAJARAN GEOMETRI MELALUI MODEL PACE BERBANTUAN GEOGEBRA - Nurfadilah Siregar; Nani Ratnaningsih (KALAMATIKA Jurnal Pendidikan Matematika, 2019)
The aim of this study is to look at students' attitudes towards Geometry learning through the PACE model assisted by GeoGebra in one of junior high school in Cimahi City. The method used in this study is descriptive qualitative with a one-shoot case study design. After students taught during Geometry learning, namely by using the PACE model assisted by GeoGebra, at the end of the learning students are given a Likert model attitude scale questionnaire containing 21 statements with four choices. The results showed that students' attitudes towards the five indicators measured all showed positive attitudes. The attitude shown by the students' answers to the proposed statements shows the positive attitude of students towards interest, seriousness, and pleasure during Geometry learning through the GeoGebra-assisted PACE model.